Interceptor® long-lasting insecticidal net: phase III evaluation over three years of household use and calibration with Phase II experimental hut outcomes. Issue 1 (December 2016) - Tungu, Patrick; Kirby, Matthew; Malima, Robert; Kisinza, William; Magesa, Stephen; Maxwell, Caroline; Batengana, Benard; Pigeon, Olivier; Rowland, Mark
Abstract Background Long-lasting insecticidal nets (LN) are an effective tool for malaria prevention. The World Health Organization Pesticide Evaluation Scheme has established evaluation criteria to facilitate registration for public use. A household randomised trial was conducted in Tanzania according to WHOPES Phase III procedures to evaluate the alpha-cypermethrin coated Interceptor® LN (BASF) over three years' use. Outcomes were calibrated against results of Phase II experimental hut trials. Methods Interceptor LN (200 mg/m2 alpha-cypermethrin) and conventionally treated nets CTN (40 mg/m2 alpha-cypermethrin) were randomly distributed to 934 households. At 6-monthly intervals, household surveys recorded net use, durability, adverse effects, user acceptance and washing practices. Concurrently, 30 nets of each type were collected and tested for knock-down and kill ofAnopheles gambiae mosquitoes in cone and tunnel bioassays. Alpha-cypermethrin content of nets was assessed annually. Results At 12 months 97 % of Interceptor LN met the efficacy criteria by cone or tunnel test; this pass rate declined to 90 % at 24 months and 87 % at 36 months. In contrast only 63 % of CTN met the efficacy criteria at 12 months, 14 % at 24 months and 0 % at 36 months. The alpha-cypermethrin content at 36 months on Interceptor LN was 20 % (42 ± 13 mg/m2 ) of the initial content but on CTNs only 4 % (1.3 ± 1.6 mg/m2 ) remained. Interceptor LN was reported to be used year-round and washed 4.3 times/year. A few recalled facial tingling during the first days of use but this did not deter usage. The average number of holes at 36 months was 18, hole area per net was 229 cm2 and hole index was 332. Insecticide content and cone bioefficacy of LN and CTN after 36 months' use were similar to that of LN and CTN used in earlier Phase II hut trials, but while the 20 times washed LN tested in experimental huts gave adequate personal protection the 20 times washed CTN did not. Conclusions More than 80 % Interceptor LN fulfilled the WHOPES Phase III criteria at 36 months and thus the LLIN was granted full WHO recommendation. Phase III outcomes at 36 months were anticipated by Phase II outcomes after 20 standardized washes.